Improvements and Setbacks in Women's Access to Education: A Case Study of Afghanistan - Kayen, Hazrat Shah (UIII Press, 2022)
Afghanistan has struggled poorly regarding women’s education since modern education was brought to the country. Over the last 26 years, women have experienced ups and downs in their access to education in Afghanistan. This study explores women’s access to education in Afghanistan across three different regimes. It was found that women across all three rules have had limited access to education given the diverse culture of the country; cultural restrictions, insecurity, lack of adequate school equipment, and distant school locations were identified as the leading causes behind women’s reduced access to education. Recently, the country experienced another overthrowing of an established government that had helped get 40 percent of women into learning spheres between 2001 and 2021. Now, Afghan women face immense uncertainty about their education in the future, even though the new Taliban regime promised to provide equal access to education. In this research, alongside other barriers to women’s entry to schooling, social and cultural ideologies were also uncovered, which have mainly hindered women’s access to education across the country.